2007
DOI: 10.1680/coma.2007.160.4.135
|View full text |Cite
|
Sign up to set email alerts
|

Life-cycle assessment and embodied energy: a review

Abstract: In this paper life-cycle assessment (LCA) is studied and a brief review and classification of databases and inventories is given. The factors affecting the dissimilar results in various databases are examined and discussed. The main obstacles to LCA and life-cycle energy studies, and their sources, are discussed, together with the role of data in inventory analysis. Embodied energy results are reviewed and compared, and the causes of dissimilarities and variations in these studies are presented. This paper foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…They constituted an iterative process where the old data were replaced with new, leading to a more realistic evaluation as is described deeper in Aranda-Usón et al [16]. In general, the LCA evaluates the overall impact of a product or service under analysis, and it is a truly holistic approach because it handles a range of different environmental impact categories [17]. However, among all the environmental impact categories that the LCA methodology can handle, the climate change category has been emphasised and fully analysed in this work because the main environmental burdens of the industrial processes are linked to greenhouse gas (GHG) emissions, as a result of the consumption of a large amount of energy to generate heat in these processes.…”
Section: Methodsmentioning
confidence: 99%
“…They constituted an iterative process where the old data were replaced with new, leading to a more realistic evaluation as is described deeper in Aranda-Usón et al [16]. In general, the LCA evaluates the overall impact of a product or service under analysis, and it is a truly holistic approach because it handles a range of different environmental impact categories [17]. However, among all the environmental impact categories that the LCA methodology can handle, the climate change category has been emphasised and fully analysed in this work because the main environmental burdens of the industrial processes are linked to greenhouse gas (GHG) emissions, as a result of the consumption of a large amount of energy to generate heat in these processes.…”
Section: Methodsmentioning
confidence: 99%
“…Life cycle analysis (LCA) is a technique employed to assess the environmental impacts of products, buildings or other services throughout their life-cycle (Menzies, 2007). In order to carry out an analysis, clearly defined boundary conditions are required to describe which parts of the material 7 production, manufacture and deployment are taken into account during an LCA analysis.…”
Section: Life Cycle Boundariesmentioning
confidence: 99%
“…Several studies [4,5] showed that it is possible to capture the EE of materials through process analysis, input-output (I/O) analysis and hybrid analysis, process analysis being more realistic with regard to main process energy omitting the remote upstream and downstream processes while I/O analysis presents a comprehensive framework including all the upstream and downstream processes with less clarity on main process energy. Existing compilation on embodied energy (EE) values for building materials include mainly open-access institutional, industrial, commercial and individual databases [4]. There are only few distinct individual studies on embodied energy assessment of common building materials.…”
Section: Earlier Investigationsmentioning
confidence: 99%